QUALITIES OF A PROFESSIONAL TRANSLATOR - Aziza Saitkhanova (Galaxy International Interdisciplinary Research Journal, 2024)
This article discusses the translator’s professional etiquette and its importance in translation process. The information about professional speed in translation and importance of fast typing as well as translation company regulations will be analyzed in the article.